2002
DOI: 10.1161/01.str.0000016344.49819.f7
|View full text |Cite
|
Sign up to set email alerts
|

Does Renal Dysfunction Predict Mortality After Acute Stroke?

Abstract: Background and Purpose-The purpose of this study was to investigate renal function as a long-term predictor of mortality in patients hospitalized for acute stroke. Methods-This was a cohort study done in a Scottish tertiary teaching hospital. Participants included 2042 (993 male) unselected consecutive stroke patients (mean age, 73 years) admitted to hospital within 48 hours of stroke between1988 and 1994. Follow-up was up to 7 years. Main outcome measure was all-cause mortality. Results-The total number of de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
112
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(132 citation statements)
references
References 22 publications
19
112
1
Order By: Relevance
“…46 This study showed that although estimated GFR was associated with increased risk, the risk was lower than that observed for cystatin C. 46 Possible reasons for the stronger association between serum cystatin C and mortality compared to creatinine and estimated GFR are not completely clear, but are likely due, at least in part, to non-GFR determinants of serum cystatin C. 47 In previous studies, it was documented that renal dysfunction is independent predictor of short-and long-term mortality in patients with stroke. [9][10][11][12][13][14] In most studies, creatinine or estimated GFR based on creatinine were used to define renal dysfunction. The predictive value of cystatin C has not been fully established in patients suffering from ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…46 This study showed that although estimated GFR was associated with increased risk, the risk was lower than that observed for cystatin C. 46 Possible reasons for the stronger association between serum cystatin C and mortality compared to creatinine and estimated GFR are not completely clear, but are likely due, at least in part, to non-GFR determinants of serum cystatin C. 47 In previous studies, it was documented that renal dysfunction is independent predictor of short-and long-term mortality in patients with stroke. [9][10][11][12][13][14] In most studies, creatinine or estimated GFR based on creatinine were used to define renal dysfunction. The predictive value of cystatin C has not been fully established in patients suffering from ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Furthermore, renal dysfunction was also an independent predictor of mortality in patients with stroke. 9,[11][12][13] Patients with renal dysfunction are also at greater risk of future ischemic stroke. 14 Estimation of the glomerular filtration rate (GFR) is essential for the evaluation of patients with kidney disease.…”
Section: Introductionmentioning
confidence: 99%
“…19 Similar relationships between kidney function and the risk for coronary heart disease and death were also found. The importance of the increased risk for stroke is highlighted by data suggesting that outcomes after stroke are particularly poor in people with early 20 or advanced CKD. 21 The use of a perindopril-based BP-lowering regimen produced a separately statistically significant 30% (95% CI 14 to 42%; P ϭ 0.002) reduction in the risk for major cardiovascular events among the 1757 participants in the PROGRESS who had CKD at baseline.…”
Section: Effects Of Perindopril-based Therapy On Cardiovascular Eventmentioning
confidence: 99%
“…In addition, in the study of Bowling et al, 31 intermittent claudication, angina pectoris, advancing age, male gender, and computed tomographic evidence of any cerebral infarct especially a watershed infarct or white matter hypodensity ¡ factors that were all present and associated with ischemic stroke in patients with intermittent claudication in our study ¡ were independent risk factors for major vascular events (stroke, myocardial infarction, or vascular death) in patients with a recent TIA or minor stroke. In another study, 23 renal dysfunction was a signi cant predictor of increased mortality in acute stroke patients in both the short-and long-term. In the present study, the early prognosis of patients with ischemic stroke with and without claudication was similar, with no differences in the percentages of in-hospital mortality (16% vs 14%) and absence of functional limitation at hospital discharge (20.5% vs 18.5%).…”
Section: Discussionmentioning
confidence: 92%